2020
DOI: 10.1103/physrevresearch.2.013209
|View full text |Cite
|
Sign up to set email alerts
|

Topological valley transport under long-range deformations

Abstract: Edge states protected by bulk topology of photonic crystals offer exciting means to study spintronics, and their robustness to short-range disorder makes robust information transfer possible. Here, we investigate topological transport under long-range amorphous deformation without external magnetic field. Vertices of each regular hexagon in a C3-symmetric crystalline structure are shifted randomly. Despite the existence of unpredictable scattering, topological edge modes are determined by statistic behavior of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Numerical studies that demonstrate the robustness of these topological states versus conventional designs for Newtonian systems are found in [50,[53][54][55]. Theoretical studies that demonstrate the existence of these modes under disorder are found in [56,57].…”
Section: D Dispersion Curves and Edge Statesmentioning
confidence: 84%
“…Numerical studies that demonstrate the robustness of these topological states versus conventional designs for Newtonian systems are found in [50,[53][54][55]. Theoretical studies that demonstrate the existence of these modes under disorder are found in [56,57].…”
Section: D Dispersion Curves and Edge Statesmentioning
confidence: 84%
“…Numerical studies that demonstrate the robustness of these topological states versus conventional designs for Newtonian systems are found in [49,[52][53][54]. Theoretical studies that demonstrate the existence of these modes under disorder are found in [55,56].…”
Section: D Dispersion Curves and Edge Statesmentioning
confidence: 84%
“…However, valley‐Hall lattices are not limited to these designs and can be realized in other settings, such as the kagome lattice, [ 71,72 ] the square lattice, [ 73–75 ] and even amorphous systems. [ 76,77 ] Due to this simplicity and flexibility in design, photonic valley‐Hall systems have been widely studied, and various new phenomena and applications have been discovered. In the next four sections, we will review several important aspects of photonic valley‐Hall systems, showing that they are simple but effective.…”
Section: Photonic Valley‐hall Systemsmentioning
confidence: 99%
“…[ 81 ] In fact, valley transport is even found to exist in systems without long‐range order. [ 76,77 ] Thus, as long as the short‐range order around the interface approximately holds, the backscattering and localization induced by disorders would not be significant, and the robustness of kink states would be approximately valid. In addition, to engineer fully topologically protected valley transport, researchers have suggested using chiral vortex in a nonlinear polariton lattice.…”
Section: Robustness Too Weak?mentioning
confidence: 99%